Unraveling the role of EPOC during the enhancement of RWGS reaction in a Pt/YSZ/Au single chamber reactor - Christos Chatzilias; Eftychia Martino; Alexandros K. Bikogiannakis; Georgios Kyriakou; Alexandros Katsaounis (Journal of CO2 Utilization)
The hydrogenation of CO2 remains one of the most intriguing and effective strategies for addressing the continuous increase of CO2 emissions in the atmosphere. At the same time, it serves as an effective pathway for the formation of value-added products. This work explores the Electrochemical Promotion of Catalysis (EPOC) phenomenon on the CO2 hydrogenation reaction, utilizing a single chamber reactor with a Pt/YSZ/Au electrochemical cell. Experiments were conducted under ambient pressure conditions, within a temperature range of 200–400 °C, for a reactant flow rate of 100 cm3/min under reducing (PCO2: PH2 = 1:7) and oxidizing (PCO2: PH2 = 2:1) conditions. The effect of reactant ratio, reactor temperature, and applied current/potentials on the reaction rate were thoroughly investigated. The only observed product was carbon monoxide through the Reverse Water Gas Shift Reaction (RWGS). Under purely catalytic operation of the cell (open circuit), reducing conditions were found to be more favorable for the RWGS reaction as compared to oxidizing ones. The imposition of negative potential values under reducing environment resulted in a 2.3-fold increase in the RWGS reaction rate (rCO = 21 × 10−9 mol/s) as compared to open circuit values (rCO = 9 × 10−9 mol/s). On the other hand, application of positive potentials had no profound effect on the catalytic rate, which was attributed to competing electrochemical and surface processes taking place on the catalyst electrode. The kinetic results are discussed in conjunction with the physicochemical and the morphological characteristics of the catalytic film.